Expression of Knowledge Sharing in Virtual Communities of Interest: A Reading Community-Based Research - Siudikienė, Daiva; Jokūbauskienė, Saulė (Information & Media, 2023)
Members of modern society, being active media users, live and carry out professional, social or leisure activities with and on the media, which changes the previously usual ways and forms of how they realize their needs and goals. In the era of digitization, various virtual communities are emerging, whose members focus on the practices of knowledge creation, processing and sharing. Virtual communities of practice have received much attention from researchers, but communities of interest are a less researched phenomenon. In the context of communities of various interests, communities of readers are active, sharing their knowledge and reading experience with each other. The article presents the conducted research, during which the aim was to investigate the expression of knowledge sharing and the factors promoting it in a reading community on the social network Facebook. With the development of social networks, the growth of various virtual communities of interest is noticeable, in which participants operate on a voluntary basis, seek to realize their various needs and participate in collective cooperation processes. Community members have been found to have the knowledge to share. This awareness of the opportunity to benefit others and the resulting feedback empowers actors to create value for the community.